1985
DOI: 10.1111/j.1365-2311.1985.tb00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Insect visitors to extrafloral nectaries of Byttneria aculeata (Sterculiaceae): relative importance and roles

Abstract: 1. Ants, parasitoids and flies are about equally frequent at foliar nectaries of Bytmeriu uculeutu (Sterculiaceae) in lowland Costa Rica during the dry season, a pattern previously unreported but also observed at other plants in the area.2. Species of Ectutommu, Cremutogaster and Camponotus were the most frequent of twenty-four ant species on Byttneriu, eight of which nested in the hollow stems. Ants spent most time at nectaries and little in patrolling.3. Collections at nectaries yielded large numbers of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Ectatomma tuberculatum also moves throughout the reproductive axis searching for EFNs, and is as effective in attacking simulated baits as is C. sericeiventris. Hespenheide (1985) also described Ectatomma ruidum as moving slower than Camponotus spp. while foraging on foliar EFNs of Byttneria aculeata, but he found no direct evidence of benefits to plants bearing ants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ectatomma tuberculatum also moves throughout the reproductive axis searching for EFNs, and is as effective in attacking simulated baits as is C. sericeiventris. Hespenheide (1985) also described Ectatomma ruidum as moving slower than Camponotus spp. while foraging on foliar EFNs of Byttneria aculeata, but he found no direct evidence of benefits to plants bearing ants.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have observed the commonness and great potential for herbivore deterrence of both the genus Camponotus (e.g., Oliveira et al, 1987;Dansa & Rocha, 1992;Costa et al, 1992;Rico-Gray, 1993), and Ectatomma (Hespenheide, 1985;Jaffe et al, 1989;Rico-Gray, 1989;Dejean & Lachaud, 1992;Rico-Gray & Thien, 1989;Peakall;1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal care in this species seems to have a clear and unambiguous selective value: as in many other subsocial insects, it lowers mortality due to predation (Tallamy and Wood 1986 (Hespenheide 1985).…”
Section: Discussionmentioning
confidence: 99%
“…in the Sterculiaceae (Hespenheide 1983(Hespenheide , 1985. Although it has not been reared, Byttneria is almost certainly the larval host.…”
mentioning
confidence: 99%